Religious Music Therapy Intervention to Reduce Pain Scale in Patients Post Orif Surgery for Sinistra Clavicle Fracture - Safito, Rayhan; Istiqomah, Istiqomah; Pranowo, Samsu (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
A fracture is a disruption of bone continuity caused by direct or indirect trauma which causes pain. The pain of post-fracture surgery patients must be treated because it disrupts the patient's life, accelerates tissue damage and thus worsens the quality of the patient's health. Nonpharmacological pain management consists of massage, ice and heat therapy, electrical nerve stimulation, distraction, relaxation, distraction techniques such as music, guided imagery, and hypnosis. One thing that can be intervened is religious music therapy. According to the register data at Dr. Sardjito Hospital, the incidence of fractures in Dahlia 1 ward at Dr. Sardjito Hospital. Sardjito in 2023 will be 92 cases. Describe the application of religious music therapy intervention to reduce the scale of pain in post-operative patients with left clavicle fractures in Dahlia Ward 1, Dr. Sardjito Hospital, Yogyakarta. The method used is a descriptive method with a case study using 1 respondent who experienced pain less than 7, collecting data using interviews and observations then providing religious music therapy for 3 days, carried out 1 day 2 times within 15 minutes each implementation.. On the first day of religious music therapy intervention, the patient's pain scale was 6, after therapy the pain scale became 4, on the second day the patient's pain scale was 3, after therapy the pain scale became 1 and on the third day the pain scale was 1 after therapy became 1 with a frequency of 2 times a day for 3 days and the duration of therapy is 15 minutes. Pain scale measurements were carried out using the Numeric Rating Scale (NRS). Based on the results of a case study conducted in Dahlia ward 1 of RSUP Dr.Sardjito Yogykarta For 3 days, it can be concluded that the provision of religious music therapy religious music therapy can reduce the scale level of pain in patient after post-operative left clavicle fracture surgery.